2014
DOI: 10.1002/wdev.168
|View full text |Cite
|
Sign up to set email alerts
|

Identifying transcriptional cis‐regulatory modules in animal genomes

Abstract: Gene expression is regulated through the activity of transcription factors and chromatin modifying proteins acting on specific DNA sequences, referred to as cis-regulatory elements. These include promoters, located at the transcription initiation sites of genes, and a variety of distal cis-regulatory modules (CRMs), the most common of which are transcriptional enhancers. Because regulated gene expression is fundamental to cell differentiation and acquisition of new cell fates, identifying, characterizing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 195 publications
(219 reference statements)
0
76
0
Order By: Relevance
“…Fortunately, methods for CRM discovery, both empirical and computational, have improved dramatically in the past several years [reviewed by 43], and examples of GRN evolution have now been observed in all of the common metazoan model species. Particularly strong examples are available from the echinoderms, due to the extensive cis -regulatory analysis that has been performed on sea urchin development [44], but several well-described vertebrate instances exist as well.…”
Section: Crm Discovery In Multiple Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, methods for CRM discovery, both empirical and computational, have improved dramatically in the past several years [reviewed by 43], and examples of GRN evolution have now been observed in all of the common metazoan model species. Particularly strong examples are available from the echinoderms, due to the extensive cis -regulatory analysis that has been performed on sea urchin development [44], but several well-described vertebrate instances exist as well.…”
Section: Crm Discovery In Multiple Speciesmentioning
confidence: 99%
“…Chromatin profiling methods have revolutionized the field of CRM discovery over the past several years, allowing for high-quality predictions of CRM location in an unbiased fashion [reviewed by 43]. Applying these methods to profile CRMs active in liver tissue across 20 mammalian species found that the majority of CRM sequences are not conserved between species [45].…”
Section: Crm Discovery In Multiple Speciesmentioning
confidence: 99%
“…Recent development of high-throughput methods for mapping protein-DNA and DNA-protein-DNA interactions has provided a relatively straightforward way to obtain instant genome-wide pictures of potential regulatory regions in any tissue or cell type of an animal (reviewed in [11,24]). However, this has raised a challenge of how to interpret these data and, more specifically, whether most of the predicted regulatory regions have any biological significance [25][26][27] highlighting the…”
Section: Importance Of Functional Transgenic Assays To Characterize Ementioning
confidence: 99%
“…They are typically a few hundred basepairs in length and can be located 5′ to, 3′ to, within introns of, or in some cases even within exons of, their target genes. Although characterizing CRMs has historically been a laborious and low-throughput activity, the advent of genome-wide approaches coupled with next-generation sequencing technologies has led to a renaissance of sorts in methods for CRM discovery (for review see [8, 1214]). However, current methods are often problematic for insects, where issues of small organism size, lack of extensive tissue-specific cell lines, and lack of mature transgenic methods for most species make these methods technically challenging and often prohibitively expensive.…”
Section: Introductionmentioning
confidence: 99%